Growth and structural changes in transition countries: The chicken or the egg? - Magdalena Olczyk; Aleksandra Kordalska (Gdańsk University of Technology, Faculty of Management and Economics, 2018)
The theoretical analysis of structural changes in the context of economic growth has a long tradition. However, studies which analyze the empirical relationship between these two economic categories are still very rare. In the literature, whether growth causes structural changes or the other way round is still an open the question. This paper empirically tests the relationship between structural changes (changes in gross value added and employment) and economic growth by using a panel Granger causality analysis based on annual data for 8 transition countries, covering the period 1995-2011. The main finding is that the causality relations analyzed are heterogeneous processes and are identified more often when we measure structural changes by value added than by changes in employment. Among the countries analyzed, we separate a subgroup of economies with very strong bilateral causality (small countries like Latvia, Lithuania, Estonia), a subgroup where no causal relationships are observed (e.g. Hungary for the case of employment) and a group with a one-directional relationship (e.g. Poland, where GDP changes cause employment changes in the Granger sense, but not vice versa).
Keywords: C12; C33; O14; O47; O57; 330; economic growth; structural changes; industries; panel data; Granger causality; CEE countries